PENGARUH KOMITE AUDIT DAN FEE AUDIT TERHADAP KUALITAS AUDIT PADA PERUSAHAAN BUMN DI INDONESIA - Pedi Riswandi; Rina Yuniarti; Subandrio Subandrio (Universitas Muhammadiyah Bengkulu, 2024)
This study aims to analyze and determine the effect of good corporate governance and audit fees on audit quality in state-owned companies listed on the Indonesia Stock Exchange in 2018-2023. This type of research is quantitative research. The sampling technique uses purposive sampling techniques with a total research sample of 75 companies. This research uses secondary data obtained through the company's annual report and financial statements during the 2018-2023 period. The analysis technique used is logistic regression analysis. The results of the study using SPSS version 25 showed that: (1) Audit committee has a negative and insignificant effect on audit quality, (2) Audit fees have a positive and significant effect on quality. Keywords: Institutional Ownership, Audit Committee, Audit Fee, Audit Quality.